2020
DOI: 10.3390/diseases8010005
|View full text |Cite
|
Sign up to set email alerts
|

Rabies: Knowledge, Attitude and Practices in and Around South Gondar, North West Ethiopia

Abstract: A cross-sectional study was conducted from February 2017 to April 2017 to assess knowledge, attitude and practices of the community towards rabies in south Gondar zone, Ethiopia. A structured closed ended questionnaire was used to collect the data through face to face interviews among 384 respondents. The data were then analyzed using SPSS statistical software version 20. Almost all (91.5%) surveyed individuals were aware of rabies. Bite was known as mode of rabies transmission by majority of the respondents (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
30
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 31 publications
12
30
6
Order By: Relevance
“…This finding was higher than the previous findings from Ethiopia [15,16], Cambodia [14], and India [17]. The study found that 99.4% of the respondents had heard about rabies, which was higher than previous findings from Ethiopia (77.9%) [15], Cambodia (86.9%) [14], Pakistan (89.4%) [18], and Bhutan (98%) [19]. This study not only highlights the need to enhance dog rabies vaccination campaigns but also reveals a high level of awareness of rabies within this endemic country.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…This finding was higher than the previous findings from Ethiopia [15,16], Cambodia [14], and India [17]. The study found that 99.4% of the respondents had heard about rabies, which was higher than previous findings from Ethiopia (77.9%) [15], Cambodia (86.9%) [14], Pakistan (89.4%) [18], and Bhutan (98%) [19]. This study not only highlights the need to enhance dog rabies vaccination campaigns but also reveals a high level of awareness of rabies within this endemic country.…”
Section: Discussioncontrasting
confidence: 89%
“…We found that all of the 175 respondents from the DRUV villages did not vaccinate their dogs against rabies. This finding was higher than the previous findings from Ethiopia [15,16], Cambodia [14], and India [17]. The study found that 99.4% of the respondents had heard about rabies, which was higher than previous findings from Ethiopia (77.9%) [15], Cambodia (86.9%) [14], Pakistan (89.4%) [18], and Bhutan (98%) [19].…”
Section: Discussioncontrasting
confidence: 74%
“…Another study done in Ethiopia[ 17 ] differs in knowledge about the fatal nature of the disease (84.6%), awareness about the prevention of rabies with vaccination (65.9%), mode of transmission, and appropriate first aid. But this study is similar in the association of the knowledge level of the participants with education and gender to our study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 8 12 13 15 17 18 ] Symptoms of paralytic rabies (weakness, loss of coordination, and paralysis), the commonest form of rabies in dogs, are not recognized by the majority of participants of this study as same as other studies on rabies. [ 7 8 12 13 15 17 18 ] It is important to educate these details to the community, especially the pet owners and animal handlers to be cautious while handling animals.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies recorded that the KAP with rabies is far better in urban residents than rural communities [ 24 ]. A better understanding of rabies knowledge in the upper-class people and higher education level may be due to their education, social contact, and self-awareness level [ 37 ]. Similar observations were also reported from Ethiopia [ 26 ].…”
Section: Discussionmentioning
confidence: 99%